Begonia erythrobracteata (Begoniaceae) a new species from the Atlantic Coastal Forest in the state of São Paulo, Brazil - Miranda, Marcelo Dias; Jacques, Eliane De Lima (Phytotaxa, 2020)
Begonia erythrobracteata (Begoniaceae) is a new, narrow endemic from the Atlantic Coastal Forest of Brazil. This species is closely related to Begonia olsoniae and B. fimbritepala and shares their rupicolous habit and transversely ovate leaf blades with a cordate base. It differs to B. fimbritepala in its petioles, which are densely squamulose along their entire length (vs. with simple trichomes) and B. olsoniae by its glabrous (vs. pilose) adaxial leaf surface. B. erythrobracteata is described and illustrated with detailed field photographs, and a provisional IUCN Red List Assessment is provided.